Effect of source and journey on physiological variables in calves transported by road and ferry between Ireland and the Netherlands - van Dijk, Luca L.; Siegmann, Susanne; Field, Niamh L.; Sugrue, Katie; van Reenen, Cornelis G.; Bokkers, Eddie A. M.; Sayers, Gearoid; Conneely, Muireann (Frontiers in Veterinary Science, 2023)
This study aimed to establish baseline variables for calves transported by road and ferry from Ireland to The Netherlands, and to investigate the effect of journey (two comparable journeys in April (J1) & May (J2) 2022) and source (source farm or mart) on these variables. A total of 66 calves from the source farm or mart were transported from Ireland to commercial veal farms in The Netherlands. Blood samples were collected at the source farm/mart, assembly centre (Ireland), lairage (France), and on arrival on the veal farm (Netherlands). Blood was analysed for indicator variables related to energy balance, hydration/electrolytes, physical/muscular stress, immunity, and inflammation (glucose, beta-hydroxy butyrate (BHB), non-esterified fatty acids (NEFA), potassium, sodium, magnesium, chloride, urea, haematocrit, total protein, creatine kinase, L-lactate, cortisol, white blood cell, neutrophil, lymphocyte and monocyte counts, serum amyloid-A, and haptoglobin). Health variables eye and nose discharge, skin tent (a measure of dehydration), and navel inflammation were scored by a trained observer, and calves were weighed at every blood-sampling timepoint. All blood variables and body weight changed significantly (P < 0.05) during transport, most notably between the assembly centre and the lairage. Reference ranges were available for eighteen variables and eleven of these variables exceeded reference ranges at the lairage while ten variables exceeded reference ranges on arrival at the veal farm. However, health variables did not change during transport. A journey-to-journey comparison indicated much variation, eighteen out of twenty-five variables differed significantly on at least one time-point. In total, J1 calves experienced a more severe change in BHB, potassium, strong-ion-difference, L-lactate, and eye and nose discharge relative to calves in J2. The source of calves also impacted their physiology, twelve out of twenty-five variables studied differed significantly, all of which were confined to the first timepoint, where mart calves had elevated levels of NEFA, Urea, haematocrit, L-lactate, cortisol, white blood cell, neutrophil, and monocyte counts and lower levels of corrected chloride and lymphocyte count. Overall, calves in this study showed a generalised physiological disturbance beyond reference limits during long distance transport, but no animal died during transport or for three weeks post arrival.